2007
DOI: 10.1093/hmg/ddm370
|View full text |Cite
|
Sign up to set email alerts
|

Point mutations in a distant sonic hedgehog cis-regulator generate a variable regulatory output responsible for preaxial polydactyly

Abstract: Precise spatial and temporal control of developmental genes is crucial during embryogenesis. Regulatory mutations that cause the misexpression of key developmental genes may underlie a number of developmental abnormalities. The congenital abnormality preaxial polydactyly, extra digits, is an example of this novel class of mutations and is caused by ectopic expression of the signalling molecule Sonic Hedgehog (SHH) in the developing limb bud. Mutations in the long-distant, limb-specific cis-regulator for SHH, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
154
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 159 publications
(168 citation statements)
references
References 35 publications
13
154
0
Order By: Relevance
“…Surprisingly, this effect was not confined to the ectopic anterior Shhexpressing region seen in the Slk leg, but was also found in the posterior Shh-expressing region of the Slk leg and wing. We, therefore, conclude that although misregulation of Shh occurs from the loss of a long-range Shh control element, as has been previously proposed (Lettice et al, , 2008, this is not an anterior specific element, but general to both the anterior and posterior regions of the limb, which have the potential to express Shh (Amano et al, 2009;Tanaka et al, 2000).…”
Section: The Po Locus Results In Allelic Imbalance and Misregulation supporting
confidence: 63%
See 4 more Smart Citations
“…Surprisingly, this effect was not confined to the ectopic anterior Shhexpressing region seen in the Slk leg, but was also found in the posterior Shh-expressing region of the Slk leg and wing. We, therefore, conclude that although misregulation of Shh occurs from the loss of a long-range Shh control element, as has been previously proposed (Lettice et al, , 2008, this is not an anterior specific element, but general to both the anterior and posterior regions of the limb, which have the potential to express Shh (Amano et al, 2009;Tanaka et al, 2000).…”
Section: The Po Locus Results In Allelic Imbalance and Misregulation supporting
confidence: 63%
“…Mutations within the ZRS have been reported to induce ectopic anterior Shh expression in the developing mouse limb Lettice et al, 2003Lettice et al, , 2008 and it has been shown that Shh is expressed ectopically in the Slk leg (Arisawa et al, 2006). On examining Shh expression in the developing Slk leg, we observed that in addition to ectopic anterior expression previously reported (Arisawa et al, 2006), the posterior Shh domain was slightly larger in Slk embryos compared to wt legs (compare Fig.…”
Section: Shh Expression Is Abnormal In Both the Anterior And Posteriosupporting
confidence: 64%
See 3 more Smart Citations